2022
DOI: 10.18063/ijb.v8i1.504
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol Jet® Printing of Poly(3,4-Ethylenedioxythiophene): Poly(Styrenesulfonate) onto Micropatterned Substrates for Neural Cells In Vitro Stimulation

Abstract: In neural tissue engineering (NTE), topographical, electrical, mechanical and/or biochemical stimulations are established methods to regulate neural cell activities in in vitro cultures. Aerosol Jet® Printing is here proposed as enabling technology to develop NTE integrated devices for electrically combined stimulations. The printability of a poly(3,4 ethylenedioxythiophene):poly(styrenesulfonate) (PEDOT: PSS) commercial ink onto a reference substrate was firstly investigated and the effect of the process para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 20 publications
1
9
0
Order By: Relevance
“…AAGO-PEDOT thin films also show well-defined square edges and a uniform black-coloured surface, but some residual ink droplets are also visible. Standard PEDOT:PSS was printed for comparison ( Figure 7 e), showing uniform printed shape, and similar results have been obtained by the same authors with other PEDOT:PSS-based solutions [ 30 , 33 ]. However, a higher print speed equal to 25 mm/s is used for this study, which is much higher than the one used in multiple studies, that is, 1 mm/s [ 60 , 61 ].…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…AAGO-PEDOT thin films also show well-defined square edges and a uniform black-coloured surface, but some residual ink droplets are also visible. Standard PEDOT:PSS was printed for comparison ( Figure 7 e), showing uniform printed shape, and similar results have been obtained by the same authors with other PEDOT:PSS-based solutions [ 30 , 33 ]. However, a higher print speed equal to 25 mm/s is used for this study, which is much higher than the one used in multiple studies, that is, 1 mm/s [ 60 , 61 ].…”
Section: Resultssupporting
confidence: 81%
“…In addition, inks from the ternary nanocomposites are formulated, and an emerging 3D printing technique, Aerosol Jet ® Printing (AJ ® P), which is a rising contactless direct write approach aimed at producing fine features on a wide range of substrates [ 31 ], is applied to analyse their printability. Developed for the printed electronics industry, this technology has been recently exploited also for bioelectronics and tissue engineering [ 32 , 33 , 34 ]. The green additives (G and AA) utilised for the GO reduction process were derived from natural and renewable sources, and the process was evaluated by UV-Vis and XRD techniques.…”
Section: Introductionmentioning
confidence: 99%
“…In our prior study, this assumption was confirmed by SEM and AFM images from osteoblast-imprinted substrates. 36 Although some other techniques such as aerosol jet and other additive manufacturing methods have provided very exciting results in terms of preparing the special topographic substrates, 51 for simulating the cells pattern due to the specific topography of cells and very tiny dimensions of cell structure, the additive manufacturing methods can not be as precise as desirable. Therefore, the cell-imprinting technique by using PDMS could be the most appropriate choice for this target.…”
Section: Resultsmentioning
confidence: 99%
“… Fabrication of printable devices for neurotechnology, in the center respectively, a 3D nanoprinted microelectrode array platform, and inkjet-printed gold electrode arrays for bioelectronic interfaces (Reproduced from Khan et al (2016) and Saleh et al (2022) ), employing: (A) Digital light processing (Reproduced from Market Business News (2023) ). (B) Aerosol jet printing (Reproduced from Seiti et al (2022) ). (C) Inkjet printing (Reproduced from Cruz et al (2018) ).…”
Section: Overview Of Printing Techniquesmentioning
confidence: 99%